Revisiting digital game-based mathematics learning: Global insights into thinking and attitudes from a PRISMA-guided review - Yulianto, Dwi; Situmeang, Muhamad Sukri; Anwar, Syahrul; Puspitasari, Nita (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines to evaluate the impact of Game-Based Learning (GBL) on students’ cognitive and affective domains in mathematics education. Seventeen empirical studies published between 2018 and early 2025 were rigorously selected based on strict criteria emphasizing methodological quality and relevance to cognitive and affective aspects of mathematics learning. The findings consistently indicate that GBL significantly enhances cognitive outcomes, including conceptual understanding, problem-solving skills, and critical thinking abilities—particularly when supported by digital tools such as augmented reality, 3D escape rooms, and gamified platforms. In addition, GBL positively influences affective outcomes by increasing student motivation, fostering more favorable attitudes toward mathematics, and reducing math anxiety. However, assessments of affective domains remain less standardized than those of cognitive outcomes. Key contextual factors such as students’ prior knowledge, the quality of game design, intervention duration, and teacher preparedness were found to be critical in determining GBL effectiveness. The review also highlights the dominance of digital GBL in resource-rich environments while recognizing the potential of non-digital adaptations in low-resource contexts. Drawing on diverse international evidence, this review underscores GBL’s potential as an innovative pedagogical strategy that effectively integrates cognitive and affective learning. Practical recommendations include culturally responsive game design, comprehensive teacher training, and equitable access to technology to ensure successful GBL implementation across varied educational settings.